If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying r + -77 = -1r + -7 Reorder the terms: -77 + r = -1r + -7 Reorder the terms: -77 + r = -7 + -1r Solving -77 + r = -7 + -1r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add 'r' to each side of the equation. -77 + r + r = -7 + -1r + r Combine like terms: r + r = 2r -77 + 2r = -7 + -1r + r Combine like terms: -1r + r = 0 -77 + 2r = -7 + 0 -77 + 2r = -7 Add '77' to each side of the equation. -77 + 77 + 2r = -7 + 77 Combine like terms: -77 + 77 = 0 0 + 2r = -7 + 77 2r = -7 + 77 Combine like terms: -7 + 77 = 70 2r = 70 Divide each side by '2'. r = 35 Simplifying r = 35
| 2+1(4+3x)=1+2x | | 14x+2=122x | | 2x+8y+9=16 | | x^2-1=1-5x | | 3x+ky=7 | | Rx+Sy=Tsolvey | | -c+3=c+97 | | (3x-53)=(2x-17) | | 5xsquared+90=0 | | x^2+2x+100=180 | | -8y-9=15 | | b+73=-b+3 | | -2y+2y=8 | | [x]=-18 | | 12x+36=-2(x) | | 10x-2(x-7)=8(x+1)+7 | | 6-2x+6x=x-3 | | 12x+36=-2(2) | | 4a^2-4a-3=0 | | 2=2x-17 | | (11x-3)+(10x+1)= | | 6x+7=-47-3 | | 12x+36=-2 | | 3x-4-5x=-10 | | 4.6+2.5= | | 1=3x-53 | | 3(x+4)-2x=-11 | | (x-9)=(2x+33) | | (3x+6xy+y^2)dx+(2x^2+3xy)dy=0 | | t*6-6=9 | | 2/3(3x-9)=11 | | 4a+9=2a-6 |